Pancreatic Islet Transplantation in Patients suffering from Type 1 diabetes - Indications, methods, possible risks and future directions: A literature review - Wolanin, Marta; Stachyra, Bartłomiej; Stawikowski, Cezary; Zielonka, Bartłomiej; Osińska, Aleksandra; Wolanin, Izabela; Madej, Karolina; Dengler, Barbara; Kowalczyk, Ilona; Krawiec, Paulina (Journal of Education, Health and Sport, 2023)
Introduction: Type 1 diabetes is a common and debilitating disease that requires regular glycemic control to prevent potentially fatal hypoglycemia. Objective: The aim of this study is to demonstrate the purpose, process, and consequences of pancreatic islet transplantation in patients with type 1 diabetes. Additionally, the results of the procedure after several years are described based on the available publications. Materials and Methods: The authors created a summary of available publications on pancreatic islet transplantation, based on databases such as PubMed and Google Scholar. Using the terms listed in the "key words" section, the authors searched for relevant information in other scientific papers to create the following review. Conclusions: Reducing the number of donors and developing alternative sources of pancreatic islet cells for transplantation is an active area of research, that promises to expand access and indications for pancreatic islet transplantation in future diabetes treatment.